The Relationship Between Nutritional Status and Age on the Incidence of Preeclampsia in Pregnant Women - Sinta Dewi, Ni Wayan; Amalia; Nurwinda Sari, Nova (Global Indonesia Health Care (GOICARE), 2025)
Background: Preeclampsia remains a significant threat during pregnancy, especially in developing countries, and is a leading cause of maternal death. The condition can adversely affect maternal and fetal health due to decreased uteroplacental perfusion, vasospasm, and endothelial damage. Purpose: This study aims to determine the relationship between nutritional status and age with the incidence of preeclampsia in pregnant women at RSUD Dr. H Abdul Moeloek Lampung Province in 2024. Methods: This study used a quantitative approach with a cross-sectional design. The population of this study were all laboring mothers with mild and severe preeclampsia complications. The sample of this study was 38 cases of mothers with mild and severe preeclampsia problems. Data were analyzed using the chi-square test. Findings: The results of the chi square test value for nutritional status with the incidence of preeclampsia are: p-value 0.046 < α (0.05) with the results of Ha accept and H0 rejected, which means that there is a relationship between nutritional status and the incidence of preeclampsia in laboring mothers in the Delima Room of Dr. H Abdul Moeloek Hospital Lampung Province in 2024, for maternal age with the incidence of preeclampsia, namely: p-value 0.013 < α (0.05) with the results of Ha accept and H0 rejected, which means there is a relationship between age and the incidence of preeclampsia in laboring mothers at Dr. H Abdul Moeloek Hospital Lampung Province in 2024. Conclusion: Nutritional status and maternal age are significantly associated with the incidence of preeclampsia in laboring mothers. These findings highlight the importance of maintaining maternal health and monitoring nutritional status during pregnancy to reduce the risk of preeclampsia and maternal mortality.